Tanggung Jawab Nafkah Oleh Suami PNS Beragama Islam Terhadap Istri yang Dicerai Berdasar PP No 10 Tahun 1983 di Wilayah Hukum Pengadilan Tinggi Agama Padang - eskarni ushalli (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2020)
Nafkah is all someone's expenses for people who are responsible for meeting the basic needs needed. Nafkah is divided into two, namely a living for oneself and Nafkah for others. One of the Nafkah for other people is to the wife as a result of marriage. Thus nafkah has a mandatory legal basis. The author uses this type of empirical juridical research, namely a study that uses materials or secondary data as initial data, then continues with primary data. The problems discussed in this paper are How is the responsibility of a husband of Muslim civil servants to divorce wives according to PP. 10 of 1983 regarding marriage and divorce for civil servants, how judges consider the responsibility for living by the husband of a Muslim civil servant towards divorced wives And How is the View of Islamic Law on PP No. 10 of 1983 and the decision of the Religious Court judge regarding the responsibility for nafkah by the husband of Muslim civil servants towards divorced wives. In this paper, the result of research is that the judge is of the opinion that this rule is not directly related to the case settlement process in court, but seen from the arguments presented in the text, it is not explained that there is a determination of the amount and period for providing nafkah, there is the way to do ijtihad or legal discovery for the sake of there is benefit.